Pemberdayaan Santripreneur melalui Produksi “D’box Crispy“ di Pondok Pesantren Sunan Drajat Lamongan - Abdul Mun'im; Abdullah As’ad; Lutfi Husain Mabruri; Misbahul Mun’im Fattah; Muh Mu’amar Al Khotimi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2021)
Santripreneurs are very important in Islamic boarding schools and at Pondok Pesantren Sunan Drajat is a boarding school located in the village of Banjarwati, Paciran sub-district which is in a large complex and is currently introducing students to the business sector. The Sunan Drajat Islamic Boarding School will later become an example for other pesantren, especially those in Lamongan and East Java in an effort to improve the quality of students who have an entrepreneurial spirit. The obstacle faced is the lack of students who have an entrepreneurial spirit. So the solution that can be given is to hold Santripreneur Empowerment through the Production of